Good Corporate Governance Dari Perspektif Islam (Analisis Komparatif Dengan Prinsip-Prinsip OECD) - Alvisa Cutyanti; Nurjanah Khofifah; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Increasing high level interest in Islamic corporate governance principles. An important ethical component of all economic activity in Islam is to ensure fairness, fairness and equality, while ensuring the rights and obligations of all parties. The Islamic economy has developed rapidly over the past two decades, with the main driver being the growth of the Islamic corporate system. This article is an attempt to discuss the nature, practice, and comparison of Islamic principles of corporate governance (IPCG) with traditional principles of corporate governance, particularly those relevant to the Organization for Economic Co-operation and Development (OECD). After discussion, it can be concluded that the Islamic aspect of corporate governance has a broader vision and, unlike the OECD, all actions and obligations cannot be divided into roles and responsibilities under the jurisdiction of Islamic sacred law. The principles apply to companies with six different concerns and obligations. In addition, this article can provide some insights on the mechanisms of control, management, and organization of economic activities from an Islamic perspective.